Kepuasan Konsumen Herlin Wedding Ditinjau dari Kualitas Produk Jasa dan Promosi : Survei pada Konsumen Herlin Wedding - Tia Risnayatu (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Wedding organizer is one of the promising and profitable businesses in Indonesia because many people need this service. Researchers use this service to conduct research. The purpose of this research is to determine the quality of service products, promotions and consumer satisfaction of Herlin Wedding, as well as to determine the effect of product quality on services and promotions on consumer satisfaction of Herlin Wedding. The method used is causality research with a survey approach. The types of data used in this research are primary data and secondary data and the analytical tools used are multiple linear regression analysis, correlation coefficient analysis and coefficient of determination analysis. The results of this data test states that there is a simultaneous significant effect on the variable quality of service products and promotions on consumer satisfaction Herlin Wedding, partially there is a significant effect on the variable quality of service and promotion products on consumer satisfaction Herlin Wedding.